Pengaruh Jumlah Penduduk, Pengangguran, dan Indeks Pembangunan Manusia terhadap Pertumbuhan Ekonomi Menurut Kabupaten/Kota di Provinsi Jawa Timur Tahun 2018-2021 - Dina Dwi Wulandari; Mulyo Hendarto Robertus (Universitas Diponegoro, 2023)
Economic growth is an indicator to measure the economic success of a region. For economic growth in East Java Province to increase, it is important to analyze the factors that influence economic growth. This study aims to analyze the effect of population, unemployment, and the Human Development Index (HDI) on economic growth in East Java Province in 2018-2021. The data used is secondary data obtained from the Badan Pusat Statistik (BPS) of East Java province. The method used in this study is multiple linear regression analysis in the form of panel data. The time series data used is 2018-2021. The cross-section data used are 38 regencies/cities in East Java Province. This study used the FEM (Fixed Effect Model) which was selected based on the Chow test and Hausman test. The results of this study indicate that population size does not affect economic growth. Unemployment has a negative and significant effect on economic growth. The Human Development Index (HDI) has a positive and significant effect on economic growth.